Interview with K.G. Kannabiren, president People's Union for Civil Liberties (PUCL), on Naxalite movement in Andhra Pradesh, interviewed by Kabir and Majumdar in Sekandrabad - Kabir, Shahriar.
Interview with K.G. Kannabiren, president People's Union for Civil Liberties (PUCL), on Naxalite movement in Andhra Pradesh, interviewed by Kabir and Majumdar in Sekandrabad.